Teacher’s and learner’s roles in autonomy-oriented foreign language teaching: a theoretical investigation (Journal of Contemporary Educational Policies and Practices, 2020)
The global language teaching community has largely spotlighted students’ autonomous learning for the last few decades. Through the thorough review of the existing literature on learner autonomy, this article aims to theoretically investigate this concept as well as clearly specify the roles played by teachers and students in an autonomy-oriented classroom. Autonomous learning is not at all synonymous with the absolute elimination of teacher’s role and learner-learner relationships. In fact, language instructors need to comprehend their roles in a multidimensional way, and students are supposed to be responsibly active for their own learning process as well as positively interdependent for academic cooperation.
Keywords: Autonomous learning; learner’s roles; teacher’s roles